Preparation method of TCO film with good electroplating liquid corrosion resistance
TCO films are prepared by using target materials composed of four types of ABCD elements and magnetron sputtering method, and adding corrosion-resistant elements to form a dense film layer, which solves the problem of corrosion of TCO films in the electroplating solution, achieving high corrosion resistance and good quality Conductive properties.
Patent Information
- Application Number
- CN202411622643.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
The existing TCO films are severely corroded in the electroplating solution, resulting in a decrease in conductivity and a decrease in transmittance, affecting the photoelectric conversion efficiency of solar cells.
TCO films are prepared by magnetron sputtering method using targets composed of four types of ABCD elements or their oxides, and corrosion-resistant elements such as Cr, Ta, Nb, etc. are added to form dense chromium oxide or tantalum oxide film layers to improve electroplating resistance Liquid corrosiveness.
It significantly improves the corrosion resistance of the TCO film, has low resistivity and good conductivity, and can maintain high transmittance and conductivity even after long-term soaking.
Smart Images

Figure BDA0005133849270000091 
Figure BDA0005133849270000121 
Figure BDA0005133849270000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of methods for preparing transparent conductive oxide films, and in particular to a method for preparing a TCO film with good corrosion resistance to electroplating solution. Background Art
[0002] Transparent Conductive Oxide (TCO) is a thin film material with high transmittance and low resistance in the visible light range. It is widely used in solar cells, flat panel displays, touch screens, antistatic coatings, energy-saving glass windows and other fields. At present, common transparent conductive oxide thin film materials include ITO (tin-doped indium oxide), AZO (aluminum-doped zinc oxide) and FTO (fluorine-doped tin oxide). Among them, ITO has become the most widely used transparent conductive material due to its advantages of high transmittance, good conductivity, excellent friction resistance and good chemical stability.
[0003] In crystalline silicon heterojunction solar cells, due to the P-μ / nc-Si:H / SiOx:H and N
[0004] -μ / nc-Si:H / SiOx:H layers have poor conductivity, so it is necessary to deposit a TCO film on the surface of both to promote the lateral and longitudinal transmission of photogenerated carriers inside the battery, usually an ITO film. In addition, in order to export the photogenerated carriers generated inside the battery to the external circuit, a metal electrode must be made on the surface of the TCO film. Usually, the metal electrode on the surface of the TCO film is prepared by screen printing silver paste. However, silver paste is expensive, with a silver price of up to 7,400 yuan / kg. The cost of silver paste accounts for more than 50% of the non-silicon cost of heterojunction batteries, and has become the biggest obstacle to reducing the non-silicon cost of heterojunction batteries.
[0005] Therefore, it is urgent to develop new electrode materials for crystalline silicon heterojunction solar cells to reduce silver paste consumption or completely remove silver and reduce non-silicon costs. At present, electroplated copper electrodes have outstanding advantages such as low cost, small grid line width, large aspect ratio, small shading area, low resistivity, good conductivity and complete silver removal. They are expected to replace traditional screen-printed silver paste electrodes and have become a recognized next-generation new electrode technology.
[0006] However, in order to prepare electroplated copper electrodes on TCO films, whether it is vertical electroplating or horizontal electroplating, the blue film with TCO film needs to be completely immersed in the copper electroplating solution. By applying current, the copper atoms of the cathode are transferred to the TCO film by electroplating under the action of the electric field, and thickened to several microns or even tens of microns to form electroplated copper grid electrodes. The electroplating process generally takes a few seconds to a few minutes or even more than ten minutes. Since the conventional copper electroplating solution is acidic, the traditional TCO film is an ITO film. After being immersed in the copper electroplating solution, the surface and edges of the ITO film will gradually be corroded by the electroplating solution as the electroplating time increases, resulting in an increase in the square resistance of the ITO film, and the transmittance first decreases and then increases, so that less sunlight is incident on the battery and the photogenerated carriers generated inside cannot be well conducted out, reducing the photoelectric conversion efficiency of the solar cell. Summary of the invention
[0007] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for preparing a TCO film with good corrosion resistance to electroplating solution, which has good corrosion resistance to electroplating solution, low resistivity and good conductivity.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing a TCO film with good corrosion resistance to electroplating solution, comprising the following steps:
[0009] The target material preparation steps are as follows: the target material is composed of four types of elements, ABCD, or their corresponding oxides, wherein, by mass percentage,
[0010] A is In2O3 powder, and the content of A is 85-95wt%,
[0011] B is a metal submicron powder or a corresponding oxide powder composed of at least one of the corrosion-resistant elements Ta, Cr, Y, Nb, La, Ti and Al, and the content of B is 3-12wt%.
[0012] C is a submicron metal powder or a corresponding oxide powder composed of at least one of the electron-donating elements W, Ce, Pr, Ta, and Nb, and the C content is 1.5-2wt%.
[0013] D is a submicron metal powder or a corresponding oxide powder composed of at least one of the sintering aids Ti, Ce, and Si, and the content of D is 0.5-1wt%,
[0014] The four powders of BCD were mixed evenly, and then deionized water was added as a dispersant, and then sand-milled to obtain the first slurry.
[0015] Add dispersant deionized water to powder A, and grind to obtain a second slurry.
[0016] The first slurry and the second slurry are evenly mixed and then spray-dried and granulated to obtain a first powder. The first powder is dried to obtain a second powder. The particle size distribution range of the second powder is D90<800nm.
[0017] The second powder is loaded into a mold, and the mold is pressed to obtain a first green body, and the first green body is cold isostatically pressed to obtain a second green body,
[0018] The second green compact is placed in a normal pressure atmosphere sintering furnace, oxygen and air are introduced into the furnace for high temperature atmosphere sintering to obtain a target material;
[0019] The sputtering coating step adopts the magnetron sputtering method, and a DC magnetron sputtering coating machine is used to sputter the target material to obtain a TCO film. The total thickness of the TCO film is 80-120nm, and the structure of the TCO film is a single-layer film.
[0020] A further technical solution is that the target material preparation step is:
[0021] Weigh the corresponding mass of four types of powders, ABCD, according to the mass percentage, and the selected powders meet the following conditions: the powder particle size D50 = 1-5um, the powder purity is more than 99.995%, the content of other impurities is less than 10ppm, the powder is spherical powder, the distribution dispersion of the powder (D90-D10) / D50 is required to be less than 2, and the specific surface area of the powder is 5-25m 2 / g, and the resistivity of the powder is less than 0.2mΩ·cm.
[0022] A further technical solution is that the target material preparation step is:
[0023] First, the BCD powder is mixed evenly, and then an appropriate amount of dispersant anhydrous ethanol is added to make the BCD powder evenly mixed, and then the powder is put into a sand mill for sand grinding for 1-3 hours. The diameter of the zirconium ball used in the sand mill is 0.6 mm. The first slurry is obtained by sand grinding with the sand mill. The solid content of the first slurry is 60-70%;
[0024] Add dispersant deionized water to the A powder, and grind for 0.5-2 hours to make it have good dispersibility, so as to obtain the second slurry, and the solid content of the second slurry is 60-80%.
[0025] A further technical solution is that the target material preparation step is:
[0026] After the first slurry and the second slurry are uniformly mixed, 0.1-1% of defoaming agent n-octanol and 1-3% of modifier polyvinyl alcohol are added by mass percentage, and ground for 0.5-2 hours to obtain a third slurry.
[0027] The third slurry is placed in a spray granulator, and subjected to spray drying and granulation treatment to obtain the first powder. The first powder is subjected to cyclone separation treatment to obtain the dried second powder.
[0028] In a further technical solution, the sputtering coating step includes:
[0029] The sputtering power density of the DC magnetron sputtering coating machine is set to 0.5-10W / cm 2 , the corresponding rotating target is 1-20KW / m, the sputtering pressure is set to 0.1-2Pa, the sputtering atmosphere is at least one of argon, oxygen and argon-hydrogen-oxygen mixed gas, and the gas purity is 3N-6N.
[0030] A further technical solution is that the target material preparation step is:
[0031] A is In2O3 powder,
[0032] The B is elemental Cr powder,
[0033] The C is expensive W2O3 powder.
[0034] The D is nano-scale SiO2 powder,
[0035] In the high temperature atmosphere sintering, W2O3 powder is oxidized to form WO3. 3+ Changes to W 6+ , and W 6+ Occupy 3+ position and provide 3 free electrons.
[0036] In a further technical solution, the target material preparation step is, by mass percentage,
[0037] The A is In2O3 powder with a content of 90wt%,
[0038] The B is 1.7wt% of Cr powder,
[0039] The C is 7.8wt% W2O3 powder,
[0040] The D is 0.3wt% Al2O3 powder and 0.2wt% Si powder,
[0041] The particle size D50 of the above four types of powders ABCD is 3 um.
[0042] A further technical solution is that in the target material preparation step, the composition of In2O3 is controlled at 90wt% by mass, thereby ensuring the transmittance and conductivity of the film, and at the same time, Cr, an element resistant to corrosion by electroplating solution, is doped to improve the corrosion resistance of the TCO film;
[0043] Cr forms a dense chromium oxide film on the surface of the TCO film in an oxidizing medium. Chromium has good passivation properties. The chromium film is easily passivated in the air and has good corrosion resistance in acidic electroplating solutions. The passivation process is as follows:
[0044] Cr+H2O→CrO2+2H + +2e - ,
[0045] The high-priced W2O3 is introduced to improve the conductivity of the film. W2O3 is oxidized to form WO3 during sintering. 3+ Changes to W 6+ , and W 6+ Occupy 3+ Position and provide 3 free electrons, the free electrons increase and the conductivity increases;
[0046] Nano-SiO2 is used as a sintering aid to improve the sintering performance, bending strength and internal microstructure of the target.
[0047] Al2O3 is used for doping to improve the transmittance of TCO film. On the one hand, Al2O3 has a high refractive index, high transmittance in visible light and near-infrared light regions, and a regularly arranged crystal structure. Al2O3 forms a more suitable refractive index gradient with the glass or silicon wafer substrate to reduce the optical reflection loss caused by the refractive index. On the other hand, Al2O3 provides excess free electrons to further improve conductivity.
[0048] In a further technical solution, the target material preparation step is, by mass percentage,
[0049] The A is In2O3 powder with a content of 93wt%,
[0050] The B is 2wt% Ta2O5 powder, 1wt% TiO2 powder, 0.7wt% Nb2O5 powder, 0.4wt% Y powder and 0.4wt% La2O3 powder,
[0051] The C is 1.3wt% and the Pr powder is 0.5wt%,
[0052] The D is 0.7wt% CeO2 powder,
[0053] The particle size D50 of the above four types of powders ABCD is 3 um.
[0054] In a further technical solution, after sputtering, due to the random distribution of the elements, the Ta and Nb elements that are not completely oxidized on the surface of the film are respectively combined with water vapor in the air, oxygen atoms or H in the plating solution. + or OH -Combined, these two elements have a high affinity, inhibiting the O 2- The diffusion of Ta2O5 and Nb2O3 forms a dense Ta2O5 film layer and a Nb2O3 film layer on the surface of the TCO film, which improves the corrosion resistance of the TCO film to the electroplating solution. The formation process of the two is as follows:
[0055] 2Ta+10OH - →Ta2O5+5H2O+10e -
[0056] Nb + H2O → NbO + 2H + +2e -
[0057] 2Nb+10OH - →Nb2O5+5H2O+10e -
[0058] During the crystallization process of the film, Ta2O5 becomes a non-spontaneous nucleation center in the early stage of crystal formation, which promotes the crystallization of the film, increases the surface energy, and effectively improves the corrosion resistance of the film to the electroplating solution;
[0059] TiO2 is used as a sintering aid to improve the bending strength of the target material and the refractive index of the film;
[0060] Y and La2O3 are used as sintering aids to improve the stability and dispersibility of the target and enhance the optical properties of the film;
[0061] Ce can increase the free electrons inside the target material and reduce the resistivity of the target material. Ce with an ion radius of 92pm 4+ Compared with In with an ionic radius of 81 pm 3+ The ionic radius of the doping points is close, and the microstrain near the doping point is small;
[0062] The standard formation enthalpy of CeO2 is large, which reduces the oxygen vacancy concentration of the film and improves the crystallization properties of the target and film;
[0063] Pr easily absorbs oxygen and loses electrons, providing more free electrons and reducing the resistivity of the film. At the same time, the praseodymium oxide formed has good corrosion resistance.
[0064] Compared with the prior art, the present invention has the following advantages: compared with the traditional 90:10 ITO film, the TCO film prepared by the present invention has good corrosion resistance to electroplating solution, low resistivity and good conductivity; after immersion for up to 10 minutes, the square resistance of the film only slightly increases, and the transmittance only slightly decreases, showing excellent corrosion resistance to electroplating solution; the present invention is used as an electrode material for a novel crystalline silicon heterojunction solar cell; the copper electrode electroplated on the TCO film of the present invention is used to replace the traditional screen-printed silver paste electrode, thereby achieving complete de-silvering and reducing the non-silicon cost of the heterojunction battery. DETAILED DESCRIPTION
[0065] Example 1
[0066] A method for preparing a TCO film having good corrosion resistance to electroplating solution comprises the following steps:
[0067] Target material preparation steps, preparation of target material,
[0068] Weigh ABCD powder according to mass percentage content,
[0069] A is In2O3 powder with a content of 90wt%,
[0070] B is 7.8wt% W2O3 powder,
[0071] C is 1.7wt% Cr powder,
[0072] D is 0.3wt% Al2O3 powder and 0.2wt% Si powder
[0073] The particle size D50 of the above four types of powders ABCD is 3 um.
[0074] Among them, the powder particle size D50 of the above four types of powders ABCD is 3um, the powder purity is more than 99.995%, the content of other impurities is less than 10ppm, the powder is spherical powder, the distribution dispersion of the powder (D90-D10) / D50 is 1.8, and the specific surface area of the powder is 15m 2 / g, and the resistivity of the powder is less than 0.18mΩ·cm.
[0075] In order to make the powder dispersed more evenly, the above BCD powder was first mixed evenly, and then an appropriate amount of dispersant anhydrous ethanol was added to mix the BCD powder evenly, and then put it into a sand mill for sand grinding for 1.5 hours. The diameter of the zirconium ball was 0.6 mm. The slurry after sand grinding obtained the first slurry, and its solid content was 63%.
[0076] Deionized water as a dispersant was added to the A powder, and then ground for 1 hour to make it have good dispersibility, thereby obtaining a second slurry, and the solid content of the second slurry was 65%.
[0077] The first slurry and the second slurry were mixed evenly, and a defoamer, octanol, was added at a content of 0.5%, and a surface modifier, polyvinyl alcohol, was added at a content of 2%, and the mixture was ground for 1 h to obtain a third slurry.
[0078] The third slurry is placed in a spray granulator for spray drying and granulation to form a dry first powder, and the first powder is subjected to cyclone separation to obtain a dry second powder, and the particle size distribution range of the second powder is D90=760nm. The second powder is placed in a mold for filling, and a first green body is obtained through compression molding. The first green body is placed in a bag, and cold isostatic pressing is performed again to obtain a second green body. The second green body is placed in a normal pressure atmosphere sintering furnace, and oxygen and air are introduced for high temperature atmosphere sintering to form a target material. The present invention can significantly improve the copper electroplating solution corrosion resistance of the corresponding thin film of the target material by adjusting the components in the target material.
[0079] The design principle of the target material formula is as follows:
[0080] In order to ensure the transmittance and conductivity of the TCO film, the composition of In2O3 needs to be controlled at 80-95wt%. This embodiment uses 90wt% In2O3 to ensure the transmittance and conductivity of the film; the corrosion resistance of the TCO film is improved by doping with Cr, an element resistant to electroplating solution. Cr can form a dense chromium oxide film on the surface of the TCO film in an oxidizing medium. In addition, chromium has good passivation properties. The chromium film is easily passivated in the air and has good corrosion resistance in the acidic electroplating solution. The passivation process is as follows:
[0081] Cr+H2O→CrO2+2H + +2e -
[0082] In order to further improve the conductivity of the film, this embodiment introduces high-priced W2O3, which can be oxidized to form WO3 during sintering. 3+ Changes to W 6+ , W 6+ Occupy 3+ position and provide 3 free electrons, the traditional Sn 4+Doping only provides one free electron. With more free electrons, the conductivity is enhanced. In order to improve the sintering performance, bending strength and other performance indicators of the target material, nano-scale SiO2 is used as a sintering aid to improve the sintering performance and internal microstructure of the target material. In order to improve the transmittance of the TCO film, Al2O3 is used for doping. On the one hand, Al2O3 has a higher refractive index, higher transmittance in the visible and near-infrared regions, and a regularly arranged crystal structure. It can form a more suitable refractive index gradient with the glass or silicon wafer substrate, reducing the optical reflection loss caused by the refractive index. On the other hand, it can provide excess free electrons to further improve the conductivity.
[0083] Sputtering coating step, preparation of TCO thin film,
[0084] The TCO thin film was prepared by coating on a glass substrate using a magnetron sputtering coater. The film thickness was 100 nm, the sputtering power was 4000 W, the sputtering pressure was 0.6 Pa, and the background vacuum was 3×10 -3 Pa or more. Then it was placed in an atmospheric environment and annealed on a heating platform at 200°C for 30 minutes. After annealing and cooling, the IWCAS film (TCO film) was sputtered on a glass substrate, and the IWCAS glass was immersed in the plating solution. The square resistance of the IWCAS film and the transmittance at T380-760nm (representing the average transmittance in the visible light region), T940nm (representing the transmittance in the near-infrared light region), and T365nm (representing the transmittance in the ultraviolet light region) were tested after the plating solution immersion time was 0min, 1min, 3min, 5min, and 10min, respectively. The relationship between the immersion time in the plating solution and the square resistance and transmittance of the IWCAS film (TCO film) was explored, and the results are shown in Table 1.
[0085]
[0086] Table 1 - Relationship between sheet resistance and transmittance of IWCAS film in Example 1 and immersion time in electroplating solution
[0087] Generally speaking, as the concentration of sulfuric acid increases, the stronger the acidity of the plating solution, the stronger the corrosion to TCO. The present invention tests the corrosion performance of the plating solution prepared with sulfuric acid at a concentration of 50g / L on the TCO film, wherein the plating solution is prepared with H2SO4 and CuSO4 solutions and commercial plating solution additive Cu-510 Mu, the concentration of sulfuric acid is 50g / L, the concentration of copper sulfate is 100g / L, and the concentration of Cu-510Mu is 5ml / L.
[0088] It can be seen from Table 1 that with the increase of immersion time, the square resistance of the IWCAS film of Example 1 changes little; when the immersion time is as long as 10 minutes, the average square resistance of the IWCAS film is only 52.6Ω / □, the change rate is only 6%, and the transmittance change rate is only 0.49%, showing good resistance to electroplating solution corrosion.
[0089] Example 2
[0090] A method for preparing a TCO film having good corrosion resistance to electroplating solution comprises the following steps:
[0091] Target material preparation steps, preparation of target material,
[0092] The preparation process of Example 2 is the same as that of Example 1, except that:
[0093] Weigh ABCD powder according to mass percentage, powder particle size D50 = 3um, where:
[0094] A is In2O3 powder with a content of 93wt%,
[0095] B is 2wt% Ta2O5 powder, 1wt% TiO2 powder, 0.7wt% Nb2O5 powder, 0.4wt% Y powder and 0.4wt% La2O3 powder,
[0096] C is 1.3wt% and Pr powder is 0.5wt%,
[0097] D is 0.7wt% CeO2 powder,
[0098] The design principle of the formula of Example 2 is as follows:
[0099] Ta2O5, TiO2, and Nb2O5 are corrosion-resistant elements. Ta and Nb can form a dense Ta2O5 film layer and a Nb2O3 film layer on the surface of the TCO film, respectively, thereby preventing the electroplating solution from corroding the TCO film.
[0100] After sputtering, due to the random distribution of elements, the Ta and Nb elements that are not completely oxidized on the surface of the film interact with water vapor, oxygen atoms in the air or H in the plating solution. + or OH - Combined, these two elements have a high affinity, inhibiting the O 2- The diffusion of can form a dense Ta2O5 film layer and Nb2O3 film layer on the surface of the TCO film, improving the corrosion resistance of the TCO film to the electroplating solution. The formation mechanism of the two is as follows:
[0101] 2Ta+10OH -→Ta2O5+5H2O+10e -
[0102] Nb + H2O → NbO + 2H + +2e -
[0103] 2Nb+10OH - →Nb2O5+5H2O+10e -
[0104] In addition, during the crystallization process of the film, Ta2O5 can become a non-spontaneous nucleation center in the early stage of crystal formation, promote film crystallization, increase surface energy, and effectively improve the film's corrosion resistance to electroplating solutions. TiO2 can also be used as a sintering aid to increase the bending strength of the target and the refractive index of the film. Y and La2O3 as sintering aids can improve the stability and dispersibility of the target and improve the optical properties of the film. Ce can increase the free electrons inside the target, reduce the resistivity of the target, and Ce 4+ The ionic radius (92 pm) is similar to that of In 3+ The ion radius of CeO2 is close to that of CeO2 (81 pm), and the microstrain near the doping point is small. In addition, the standard formation enthalpy of CeO2 is large, which can reduce the oxygen vacancy concentration of the film and improve the crystallization properties of the target and film. Pr easily absorbs oxygen and loses electrons, providing more free electrons and reducing the resistivity of the film. At the same time, praseodymium oxide has good corrosion resistance.
[0105] Sputtering coating step, preparation of TCO thin film,
[0106] The sputtering coating steps of Example 2 are the same as those of Example 1. A magnetron sputtering coating machine is used to sputter coat the glass substrate, and an ITTNPYCL film (TCO film) is obtained after annealing. The film thickness is 100 nm. Finally, it is immersed in a plating solution, and the sheet resistance of the ITTNPYCL film and the transmittance at T380-760nm, T940nm, and T365nm are tested after the plating solution immersion time is 0 min, 1 min, 3 min, 5 min, and 10 min, respectively. The relationship between the plating solution immersion time and the sheet resistance and transmittance of the ITTNPYCL film (TCO film) is explored, and the results are shown in Table 2.
[0107]
[0108] Table 2 - Relationship between sheet resistance and transmittance of ITTNPYCL film of Example 2 and immersion time in electroplating solution
[0109] Generally speaking, as the concentration of sulfuric acid increases, the stronger the acidity of the plating solution, the stronger the corrosion to TCO. The present invention tests the corrosion performance of the plating solution prepared with sulfuric acid at a concentration of 50g / L on the TCO film, wherein the plating solution is prepared with H2SO4 and CuSO4 solutions and commercial plating solution additive Cu-510 Mu, the concentration of sulfuric acid is 50g / L, the concentration of copper sulfate is 100g / L, and the concentration of Cu-510Mu is 5ml / L.
[0110] It can be seen from Table 2 that with the increase of immersion time, the square resistance of the ITTNPYCL film of Example 2 changes little; when the immersion time is as long as 10 minutes, the average square resistance of the ITTNPYCL film is only 66.2Ω / □, the change rate is only 6.3%, and the transmittance change rate is only 0.35%. The average transmittance in the visible light region T380-760 is as high as 84.5%, showing good resistance to electroplating solution corrosion and light transmittance.
[0111] Comparative Example 1
[0112] Target preparation:
[0113] Powders of corresponding mass were weighed according to the ratio of In2O3 content being 90wt% and the rest being SnO2 (10wt%), and the rest of the steps were the same as in Example 1.
[0114] Film preparation:
[0115] A 90:10 ITO film was sputtered on glass, using the same parameters as in Example 1, and the total thickness of the film was 100 nm. Without annealing, it was immersed in the plating solution, and the square resistance of the ITO film and the transmittance at T380-760nm, T940nm, and T365nm were tested after the immersion time of the plating solution was 0min, 1min, 3min, 5min, and 10min, respectively, to explore the relationship between the immersion time of the plating solution and the square resistance and transmittance of the ITO film, and the results are shown in Table 3.
[0116] Note: Pure glass substrate is not conductive, and the transmittance is T380-760 = 92.3%, T940 = 92.4%, T365 = 91.6%
[0117]
[0118] Table 3 - Relationship between sheet resistance and transmittance of 90:10 ITO film of comparative example 1 and immersion time in electroplating solution
[0119] It can be seen from Table 3 that the square resistance of the unannealed 90:10 ITO film increases significantly with the increase of the immersion time in the plating solution. When the immersion time is 1 minute, the average square resistance of the film reaches 152.4Ω / □, and the square resistance change rate is as high as 33.9%. When the immersion time reaches 5 minutes, the ITO film is completely corroded by the plating solution, and the film square resistance test exceeds the range. The transmittance of the film is close to that of the glass substrate, indicating that the ITO film has very poor corrosion resistance to the plating solution.
[0120] Comparative Example 2
[0121] A 90:10 ITO film with a total thickness of 100 nm was sputtered on the glass, and then annealed at 200°C in a hot stage atmosphere for 30 min. After annealing and cooling, the ITO glass was immersed in the plating solution, and the square resistance of the ITO film and the transmittance at T380-760nm, T940nm, and T365nm were tested after the plating solution immersion time was 0 min, 1 min, 3 min, 5 min, and 10 min, respectively. The relationship between the plating solution immersion time and the square resistance and transmittance of the ITO film was explored, and the results are shown in Table 4.
[0122]
[0123] Table 4 - Relationship between sheet resistance and transmittance of 90:10 ITO film of comparative example 2 and immersion time in electroplating solution
[0124] It can be seen from Table 4 that the square resistance of the 90:10 ITO film after annealing increases with the increase of the immersion time in the plating solution. When the immersion time is 1 minute, the average square resistance of the film reaches 273.6Ω / □, and the square resistance change rate is as high as 327.2%. When the immersion time is only 3 minutes, the ITO film has been completely corroded by the plating solution, and the film square resistance test exceeds the range. The transmittance of the film is close to that of the glass substrate, indicating that the annealed ITO film has very poor corrosion resistance to the plating solution.
Claims
1. A method for preparing a TCO film having good corrosion resistance to electroplating solution, characterized in that: The following steps are included: The target material preparation steps are as follows: the target material is composed of four types of elements, ABCD, or their corresponding oxides, wherein, by mass percentage, A is In2O3 powder, and the content of A is 85-95wt%, B is a metal submicron powder or a corresponding oxide powder composed of at least one of the corrosion-resistant elements Ta, Cr, Y, Nb, La, Ti and Al, and the content of B is 3-12wt%. C is a submicron metal powder or a corresponding oxide powder composed of at least one of the electron-donating elements W, Ce, Pr, Ta, and Nb, and the C content is 1.5-2wt%. D is a submicron metal powder or a corresponding oxide powder composed of at least one of the sintering aids Ti, Ce, and Si, and the content of D is 0.5-1wt%, The four powders of BCD were mixed evenly, and then deionized water was added as a dispersant, and then sand-milled to obtain the first slurry. Add dispersant deionized water to powder A, and grind to obtain a second slurry. The first slurry and the second slurry are evenly mixed and then spray-dried and granulated to obtain a first powder. The first powder is dried to obtain a second powder. The particle size distribution range of the second powder is D90<800nm. The second powder is loaded into a mold, and the mold is pressed to obtain a first green body, and the first green body is cold isostatically pressed to obtain a second green body, The second green compact is placed in a normal pressure atmosphere sintering furnace, oxygen and air are introduced into the furnace for high temperature atmosphere sintering to obtain a target material; The sputtering coating step adopts the magnetron sputtering method, and a DC magnetron sputtering coating machine is used to sputter the target material to obtain a TCO film. The total thickness of the TCO film is 80-120nm, and the structure of the TCO film is a single-layer film.
2. The method for preparing a TCO film having good corrosion resistance to electroplating solution according to claim 1, characterized in that: The target material preparation step, Weigh the corresponding mass of four types of powders, ABCD, according to the mass percentage, and the selected powders meet the following conditions: the powder particle size D50 = 1-5um, the powder purity is more than 99.995%, the content of other impurities is less than 10ppm, the powder is spherical powder, the distribution dispersion of the powder (D90-D10) / D50 is required to be less than 2, and the specific surface area of the powder is 5-25m 2 / g, and the resistivity of the powder is less than 0.2mΩ·cm.
3. The method for preparing a TCO film having good corrosion resistance to electroplating solution according to claim 1, characterized in that: The target material preparation step, First, the BCD powder is mixed evenly, and then an appropriate amount of dispersant anhydrous ethanol is added to make the BCD powder evenly mixed, and then the powder is put into a sand mill for sand grinding for 1-3 hours. The diameter of the zirconium ball used in the sand mill is 0.6 mm. The first slurry is obtained by sand grinding with the sand mill. The solid content of the first slurry is 60-70%; Add deionized water as a dispersant to the A powder, and grind for 0.5-2 hours to make it have good dispersibility, so as to obtain the second slurry, and the solid content of the second slurry is 60-80%.
4. The method for preparing a TCO film having good corrosion resistance to electroplating solution according to claim 1, characterized in that: The target material preparation step, After the first slurry and the second slurry are uniformly mixed, 0.1-1% of defoaming agent n-octanol and 1-3% of modifier polyvinyl alcohol are added by mass percentage, and ground for 0.5-2 hours to obtain a third slurry. The third slurry is placed in a spray granulator, and subjected to spray drying and granulation treatment to obtain the first powder. The first powder is subjected to cyclone separation treatment to obtain the dried second powder.
5. The method for preparing a TCO film having good corrosion resistance to electroplating solution according to claim 1, characterized in that: The sputtering coating step, The sputtering power density of the DC magnetron sputtering coating machine is set to 0.5-10W / cm 2 , the corresponding rotating target is 1-20KW / m, the sputtering pressure is set to 0.1-2Pa, the sputtering atmosphere is at least one of argon, oxygen and argon-hydrogen-oxygen mixed gas, and the gas purity is 3N-6N.
6. The method for preparing a TCO film having good corrosion resistance to electroplating solution according to claim 1, characterized in that: The target material preparation step, A is In2O3 powder, The B is elemental Cr powder, The C is expensive W2O3 powder. The D is nano-scale SiO2 powder, In the high temperature atmosphere sintering, W2O3 powder is oxidized to form WO3. 3+ Changes to W 6+ , and W 6+ Occupy 3+ position and provide 3 free electrons.
7. The method for preparing a TCO film having good corrosion resistance to electroplating solution according to claim 6, characterized in that: The target material preparation steps are as follows, by mass percentage: The A is In2O3 powder with a content of 90wt%, The B is 1.7wt% of Cr powder, The C is 7.8wt% W2O3 powder, The D is 0.3wt% Al2O3 powder and 0.2wt% Si powder, The particle size D50 of the above four types of powders ABCD is 3 um.
8. The method for preparing a TCO film having good corrosion resistance to electroplating solution according to any one of claims 1 to 7, characterized in that: The target material preparation step, The content of In2O3 is controlled at 90wt% by mass, which ensures the transmittance and conductivity of the film. At the same time, Cr, an element resistant to corrosion by electroplating solution, is used for doping to improve the corrosion resistance of the TCO film. Cr forms a dense chromium oxide film on the surface of the TCO film in an oxidizing medium. Chromium has good passivation properties. The chromium film is easily passivated in the air and has good corrosion resistance in acidic electroplating solutions. The passivation process is as follows: <h2 style=";text-align:left;direction:ltr">Cr+H2O→CrO2+2H<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> +2e<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> , The high-priced W2O3 is introduced to improve the conductivity of the film. W2O3 is oxidized to form WO3 during sintering. 3+ Changes to W 6+ , and W 6+ Occupy 3+ Position and provide 3 free electrons, the free electrons increase and the conductivity increases; Nano-SiO2 is used as a sintering aid to improve the sintering performance, bending strength and internal microstructure of the target. Al2O3 is used for doping to improve the transmittance of TCO film. On the one hand, Al2O3 has a high refractive index, high transmittance in visible light and near-infrared light regions, and a regularly arranged crystal structure. Al2O3 forms a more suitable refractive index gradient with the glass or silicon wafer substrate to reduce the optical reflection loss caused by the refractive index. On the other hand, Al2O3 provides excess free electrons to further improve conductivity.
9. A method for preparing a TCO film having good corrosion resistance to electroplating solution according to any one of claims 1 to 5, characterized in that: The target material preparation steps are as follows, by mass percentage: The A is In2O3 powder with a content of 93wt%, The B is 2wt% Ta2O5 powder, 1wt% TiO2 powder, 0.7wt% Nb2O5 powder, 0.4wt% Y powder and 0.4wt% La2O3 powder, The C is 1.3wt% and the Pr powder is 0.5wt%, The D is 0.7wt% CeO2 powder, The particle size D50 of the above four types of powders ABCD is 3 um.
10. The method for preparing a TCO film having good corrosion resistance to electroplating solution according to claim 9, characterized in that: After sputtering, due to the random distribution of elements, the Ta and Nb elements that are not completely oxidized on the surface of the film are respectively reacted with water vapor in the air, oxygen atoms or H in the plating solution. + or OH - Combined, these two elements have a high affinity, inhibiting the O 2- The diffusion of Ta2O5 and Nb2O3 forms a dense Ta2O5 and Nb2O3 film layer on the surface of the TCO film, which improves the corrosion resistance of the TCO film to the electroplating solution. The formation process of the two is as follows: 2Ta+10OH - →Ta2O5+5H2O+10e - <h2 style=";text-align:left;direction:ltr">Nb+H2O→NbO+2H<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> +2e<h2 style=";text-align:left;direction:ltr"> - 2Nb+10OH - →Nb2O5+5H2O+10e - During the crystallization process of the film, Ta2O5 becomes a non-spontaneous nucleation center in the early stage of crystal formation, which promotes the crystallization of the film, increases the surface energy, and effectively improves the corrosion resistance of the film to the electroplating solution; TiO2 is used as a sintering aid to improve the bending strength of the target material and the refractive index of the film; Y and La2O3 are used as sintering aids to improve the stability and dispersibility of the target and enhance the optical properties of the film; Ce can increase the free electrons inside the target material and reduce the resistivity of the target material. Ce with an ion radius of 92pm 4+ Compared with In with an ionic radius of 81 pm 3+ The ionic radius of the doping points is close, and the microstrain near the doping point is small; The standard formation enthalpy of CeO2 is large, which reduces the oxygen vacancy concentration of the film and improves the crystallization properties of the target and film; Pr easily absorbs oxygen and loses electrons, providing more free electrons and reducing the resistivity of the film. At the same time, the praseodymium oxide formed has good corrosion resistance.
Citation Information
Cited By
Indium titanium cerium niobium oxide ceramic target material, preparation method and application thereof, and transparent conductive oxide film
CN119613090A